FEMINIST PERSPECTIVES IN BHARTI MUKHERJEE’S NOVELS - Ms. Chandni D Pandya; Jaiminibahen Chaudhary (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper focuses the view on Feminist Perspectives in Bharti Mukherjee’s Novels. During pre-independence number of Indians migrate to colonies of Europe and other countries. Diaspora dream figures are found prominently in all the fiction of Bharati Mukherjee covering many moods of expatriation - nostalgia, uncertainty, frustration and despondency. In her novels, she explores the motif of expatriation, immigration and transformation. The challenges and issues pertaining to South Asian women, especially those in India, are the focus of Third World feminist author Bharti Mukherjee. Like her modern feminist writers, she supports women's rights, but she is different from them in that she focuses on highlighting the issues of cross-cultural conflicts that Indian women immigrants experience. Tara Banerjee in "The Tiger's Daughter," Dimple in "Wife," Jyoti in "Jasmine," the three sisters Tara, Parvati, and Padma in "Desirable Daughters," and Tara in "The Tree Bride" are all examples of this. The heroines of Bharti Mukherjee are fearless and self-assured. They have a tremendous capacity for adaptation; they embrace the harsh realities of their lives and live firmly in reality.